Processing and storage of salted dried herring (Sardinella longiceps) - Puertollano, Carmen L. (1959)
The aim of this study is to determine the effect of varying amounts of Sorbistat-K on keeping the quality and acceptability of salted dried herring (tamban). Ten kilograms of herring were salted for five hours in a 23-degree Baume brine made from impure solar salt. The fish was divided into four equal batches by weight. To partially remove the salt, each batch was immersed in fresh water containing 0.1, 0.3 and 0.5 percent Sorbistat-K for varying periods - 0, 30, 60, 90 and 120 minutes. The fish was then dried intermittently under the sun. The actual drying process covered a period of twenty-six hours. One-half of the sample was packed in a sealed moisture-proof cellophane bag. The other half was packed in an unsealed moisture-proof cellophane bag. Moisture and sodium chloride content of the dried samples were analyzed immediately after drying.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fish, Dried; Fishery processing